Penerapan Modifikasi Algoritma Trithemius Pada Aplikasi Penyimpanan File Secara Online - Andriaman Purba; Nelly Astuti Hasibuan (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
The more time is developing, the more knowledgeable, as well as file storage. As is known at this time very many people save files online because it is easy to access anytime and anywhere only with capital, but the drawback of online storage is the security that can be unsettling to users at any point of online storage. So the authors use one of the Cryptographic Algorithms, namely the Modification of the Trithemius Algorithm to carry out the security of files stored on online media. This algorithm can change the code by encrypting files. It is hoped that the community will apply or use the Trithemius Algorithm modification in order to help the community in securing files, especially important files.